The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s11295-015-0908-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and expression analysis of the amino acid transporter gene family in poplar

Abstract: Members of the amino acid transporters (AATs) gene family transported amino acid across cellular membranes and participated in various aspects of normal plant growth and developmental processes as well as environmental responses. To date, no overall analysis or expression profiling of the AAT gene family in Populus has been reported. An investigation of the Populus genome revealed 100 putative AAT genes. These genes were classified into 11 subfamilies based on phylogenetic analysis. In each subfamily, the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 68 publications
2
33
0
Order By: Relevance
“…AAPs are highly regulated by environmental signals (Grallath et al, 2005). The PtAAT genes might play a critical role in abiotic stress signaling in Populus, because their expression was either increased or repressed after the PEG and cold treatments (Wu et al, 2015). However, little is known about the role of the OsAAT alternative splicing genes in response to environmental signal, especially N in the roots and leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAPs are highly regulated by environmental signals (Grallath et al, 2005). The PtAAT genes might play a critical role in abiotic stress signaling in Populus, because their expression was either increased or repressed after the PEG and cold treatments (Wu et al, 2015). However, little is known about the role of the OsAAT alternative splicing genes in response to environmental signal, especially N in the roots and leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The AAT gene family members have been identified in Arabidopsis (Tegeder, 2012), rice (Lu et al, 2012), poplar (Wu et al, 2015), Solanum tuberosum L. (Ma et al, 2016) and Glycine max L. (Cheng et al, 2016). This showed that AAP transporters play an important role in loading of amino acids for nitrogen sink and supply (Tegeder and Ward, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Three candidate genes Potri.004G111400, Potri.T021600, and Potri.012G082800 were identified in all above analysis. The gene PtAAAP19 (Potri.004G111400) encodes transmembrane amino acid transporter family protein [32], and its homologous gene in A. thaliana involves in adventitious root formation through the uptake of neutral and acidic amino acids in roots [33]. qRT-PCR analysis indicated that PtAAAP19 exhibited higher expression levels in fine rooting genotypes (ʹTongliao1ʹ, G1, G2, and G3) than poor rooting (ʹDanhongʹ, B1, B2, and B3) ( Figure 8C).…”
Section: Genes Involved Potentially In Regulating Adventitious Root Amentioning
confidence: 99%
“…It was revealed that the C-repeat binding factor (CBF) mediated the gene expression pattern in E. guineensis under cold stress via RNA-Seq analysis [26]. Other reports indicated that the PtAAT genes might play a critical role in the abiotic stress signaling in Populus because their expression was either increased or repressed after the cold and PEG treatments [11]. However, little is known about the role of EgAAPs in response to environmental signals.…”
Section: Cold Stress Effects On the Expression Profiles Of Amino Acidmentioning
confidence: 99%
“…Furthermore, AAT families have also been identified in poplar [11], Solanum tuberosum L. [12] and Glycine max L. [13]. Importantly, studies have shown that amino acid permeases (AAPs), which belong to the AAT family [14][15][16], played an important role in loading amino acids for nitrogen sink and supply [17].…”
Section: Introductionmentioning
confidence: 99%